127k views
2 votes
Directions in the picture. we need to do number 2

Directions in the picture. we need to do number 2-example-1

1 Answer

7 votes

f(x) = (2x) ^ 1/3

g(x) = -11 ( 2x) ^ 1/3

(f+ g) (x) = (2x) ^ 1/3 + -11 ( 2x) ^ 1/3 = -10 ( 2x) ^ 1/3

(f-g) (x) = (2x) ^ 1/3 - -11 ( 2x) ^ 1/3 = (2x) ^ 1/3 + 11 ( 2x) ^ 1/3 = 12 ( 2x) ^ 1/3

The domain for (f+ g) (x) and ( f-g)(x) is all real number since there is no value that x cannot take

(f+ g) (-4) = -10 8( 2*-4) ^ 1/3 = -10 ( -8)^1/3 = -10* (-2) =20

(f-g) (-4) = 12 ( 2*-4) ^ 1/3 = 12 (-2) = -24

User Mats Lind
by
4.9k points